2002
DOI: 10.1113/jphysiol.2001.013087
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and behaviour of glabrous cutaneous receptors in the human foot sole

Abstract: Figure 4. Measuring directional sensitivity of the SAII receptor in the heelAn example of directional sensitivity for one of the SAII receptors located in the heel is presented. A handheld force transducer stretched the plantar skin of the foot in an attempt to ensure reproducible amounts of stretch. This figure shows the level of stretch applied to the skin and the corresponding discharge activity in response to anterior stretch (A), medial stretch (B), posterior stretch (C) and lateral skin stretch (D).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
254
4
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(275 citation statements)
references
References 30 publications
13
254
4
4
Order By: Relevance
“…Somatosensory information from the ankle and foot was reported to be important in the postural control [29][30][31]. Here, as in a previous study, sway was worse in the most difficult balance tasks [27].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Somatosensory information from the ankle and foot was reported to be important in the postural control [29][30][31]. Here, as in a previous study, sway was worse in the most difficult balance tasks [27].…”
Section: Discussionsupporting
confidence: 71%
“…The basic purpose of shoe inserts is to change the pressure distribution across the foot and relieve overall pain [21,28]. A secondary consideration is balance since somatosensory information from the ankle and feet is important in the postural control [29][30][31]. Off the shelf inserts are cheaper and often initially more comfortable than custom orthotics but may not provide the same kind of support that would come from an orthotic made specifically for the wearer [32].…”
Section: Discussionmentioning
confidence: 99%
“…These results supported the hypothesis that the spikes provide relevant tactile information about body position in reference to verticality. As slow adapting receptors code the continuous pressures applied to their field (Kennedy and Inglis 2002), it can be suggested that the spikes are another indented surface that increased the body awareness and improved the spatial representation of the pressure distribution under the feet sole (Wu and Chiang 1997;Kavounoudias et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Different types of mechanoreceptors [plantarsurface (PS) and deep receptors] are involved and are widely distributed under the foot sole (Kennedy and Inglis 2002). As the feet interface directly with the ground, cutaneous cues provide very detailed spatial and temporal information about the support surface properties, and about the variations of pressure under the feet that directly result from a shift of the centre of foot pressure (CoP) displacements (Maurer et al 2001;Perry 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Glabrous cutaneous receptors in these areas do not display background activity when unloaded. 29 Even more important is the observation that the frequency of slowly adapting mechanoreceptors rapidly reaches a plateau with an increased pressure. 30 This suggests that the more important pressure values and larger contact areas for the obese persons may perturb the sensory information arising from the slow adapting plantar receptors.…”
Section: Discussionmentioning
confidence: 99%